Native work : an impulse of tenderness - Putter, Andrew (Michaelis School of Fine Art, 2015)
Native Work is an installation-artwork consisting of 38 portrait photographs. It was made in response to an encounter with the archive of Alfred Martin Duggan-Cronin’s photographs of black southern Africans taken between 1919 and 1939. In its creative focus on traditional black South African culture in a post-apartheid context, Native Work is one of a series of related - but independent - projects occurring contemporaneously with it in the city of Cape Town (a situation examined more closely in the conclusion to this document: see p. 33). Native Work is motivated by a desire for social solidarity - a desire which emerges as a particular kind of historical possibility in the aftermath of apartheid. As such, it finds inspiration in Duggan-Cronin’s commitment to affirm the lives of those black South Africans who many of his peers would have dismissed as unworthy subjects of such attention. Native Work echoes that commitment by staying close to an impulse of tenderness discernible in Duggan-Cronin’s life-long project, and pays homage not only to Duggan-Cronin, but also to the expressive life of those who appeared in his work.